Effect Of Immersion Resin Acrylic Heat Cured On Sargassum ilicifolium as a Denture Cleanser Towards To Hardness Surface - Ajeng Erlinda Muchtar; Widaningsih; Anindita Apsari (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Background: Heat cured acrylic resin is a material that has been used as a base for dentures. The main recruitment of ideal dentures include esthetic, durable, and also the how hard the surface itself. A dirty denture can lead to smell of the mouth, unesthetic, and inflammatory in the oral cavity. One of the material denture cleanser made of natural can inhibit the growth of fungal contained in Sargassum ilicifolium that have content of Mg, Na, Fe, and Fenol. Purpose: The aimed of this research is to understand the effect of soaking heat cured acrylic resin as the dentures material in 40% Sargassum ilicifolium towards the hardness surface. Methods: 20 plates of 65 x 10 x 2,5 mm heat cured acrylic divided into 4 different group as samples. First group soaked for 270 hours in aquades, second group soaked for 630 hours in aquades, third group soaked for 270 hours in 40% Sargassum ilicifolium extract, and the fourth group soaked for 630 hours in 40% Sargassum ilicifolium extract. The time of the research 270 hours equivalent of the use of the denture for 3 years, 630 hours equivalent of the use of the denture for 7 years. Then, researcher tested the hardness of all four group surface using Vickers Hardness Tester by using 0,20 kg indenter weight. Result: The result of Kruskal Wallis parametric description showed that there is a difference number of the surface hardness between Aquades and Sargassum ilicifolium 40%. Mann Whitney test result also showed that there are significant number each groups Aquades and Sargassum ilicifolium. Conclusion: A number of the hardness surface of heat cured acrylic resin were soaked using 40% Sargassum ilicifolium extract for 630 hours is lower than compared heat cured acrylic resin were soaked using 40% Sargassum ilicifolium extract for 270 hours.